The frequency of differentiated CD3+CD27-CD28- T cells predicts response to CART cell therapy in diffuse large B-cell lymphoma - Worel, Nina; Grabmeier-Pfistershammer, Katharina; Kratzer, Bernhard; Schlager, Martina; Tanzmann, Andreas; Rottal, Arno; Körmöczi, Ulrike; Porpaczy, Edit; Staber, Philipp B.; Skrabs, Cathrin; Herkner, Harald; Gudipati, Venugopal; et al. (Frontiers in Immunology, 2023)
Background Chimeric antigen receptor T (CART) cell therapy targeting the B cell specific differentiation antigen CD19 has shown clinical efficacy in a subset of relapsed/refractory (r/r) diffuse large B cell lymphoma (DLBCL) patients. Despite this heterogeneous response, blood pre-infusion biomarkers predicting responsiveness to CART cell therapy are currently understudied. Methods Blood cell and serum markers, along with clinical data of DLBCL patients who were scheduled for CART cell therapy were evaluated to search for biomarkers predicting CART cell responsiveness. Findings Compared to healthy controls (n=24), DLBCL patients (n=33) showed significant lymphopenia, due to low CD3+CD4+ T helper and CD3-CD56+ NK cell counts, while cytotoxic CD3+CD8+ T cell counts were similar. Although lymphopenic, DLBCL patients had significantly more activated HLA-DR+ (P=0.005) blood T cells and a higher frequency of differentiated CD3+CD27-CD28- (28.7 ± 19.0% versus 6.6 ± 5.8%; P<0.001) T cells. Twenty-six patients were infused with CART cells (median 81 days after leukapheresis) and were analyzed for the overall response (OR) 3 months later. Univariate and multivariate regression analyses showed that low levels of differentiated CD3+CD27-CD28- T cells (23.3 ± 19.3% versus 35.1 ± 18.0%) were independently associated with OR. This association was even more pronounced when patients were stratified for complete remission (CR versus non-CR: 13.7 ± 11.7% versus 37.7 ± 17.4%, P=0.001). A cut-off value of ≤ 18% of CD3+CD27-CD28- T cells predicted CR at 12 months with high accuracy (P<0.001). In vitro, CD3+CD8+CD27-CD28- compared to CD3+CD8+CD27+CD28+ CART cells displayed similar CD19+ target cell-specific cytotoxicity, but were hypoproliferative and produced less cytotoxic cytokines (IFN-γ and TNF-α). CD3+CD8+ T cells outperformed CD3+CD4+ T cells 3- to 6-fold in terms of their ability to kill CD19+ target cells. Interpretation Low frequency of differentiated CD3+CD27-CD28- T cells at leukapheresis represents a novel pre-infusion blood biomarker predicting a favorable response to CART cell treatment in r/r DLBCL patients.